Akses Layanan Pendidikan: Ekspresi Keberagaman Anak-anak Penghayat Kepercayaan Komunitas Orang Lom - Michael Jeffri Sinabutar; Tiara Ramadhani; Waldimer Pasaribu (Universitas Batanghari Jambi, 2022)
One of the basic rights of every citizen is to obtain educational services, as stated in the preamble to the 1945 Constitution. Law Number 20 of 2003 concerning the National Education System article 12 paragraph 1 letter a mandates that every student in the education unit receives religious education according to the religion prescribed by him, adhered to and taught by religious educators within the same religion. After the decision of the Constitutional Court of MK Number 97/PUU-XIV/2016 and the Regulation of the Minister of Education and Culture 27 of 2016 became a new spirit and opportunities for believers in Indonesia. The Constitutional Court's decision did not eliminate the problems experienced by believers in relation to access to education. The guarantee of religious and moral education services for children of spiritual beliefs in accordance with their own beliefs based on article 8 paragraph 4 about the Covenant on Social and Political Rights becomes substantial in accessing religious education services. This study seeks to figure out the dynamics of the implementation of religious education services and practices experienced by children of spiritual beliefs and community strategies in gaining access to educational services.